δ-Cadinene,Calarene and δ-4-Carene from Kadsura heteroclita Essential Oil as Novel Larvicides Against Malaria, Dengue and Filariasis Mosquitoes - Govindarajan, Marimuthu; Rajeswary, Mohan; Benelli, Giovanni (Combinatorial Chemistry & High Throughput Screening, 2016)
Mosquitoes (Diptera: Culicidae) are major vectors of important pathogens and parasites. Malaria, dengue fever, yellow fever, filariasis, schistosomiasis and Japanese encephalitis cause millions of deaths every year. Mosquito control is being challenging due to the development of pesticide resistance and negative environmental concerns. In this scenario, plants employed in traditional Asian medicine may be alternative sources of newer and effective mosquitocides. In this research, we evaluated the larvicidal activity of Kadsura heteroclita leaf essential oil (EO) and its major chemical constituents (δ-Cadinene, Calarene and δ-4-Carene) against the malaria vector Anopheles stephensi, the dengue vector Aedes aegypti and the filariasis vector Culex quinquefasciatus. The chemical composition of the EO was analyzed by gas chromatography–mass spectroscopy. GC-MS revealed that the essential oil of K. heteroclita contained 33 compounds. The major chemical components were δ-Cadinene (18.3%), Calarene (14.8%) and δ-4-Carene (12.5%). The EO had a significant toxic effect against early third-stage larvae of An. stephensi, Ae. aegypti and Cx. quinquefasciatus, with LC50 values of 102.86, 111.79 and 121.97 µg/mL. The three major constituents extracted from the K. heteroclita EO were tested individually for acute toxicity against larvae of the three mosquito vectors. δ-Cadinene, Calarene and δ-4-Carene appeared most effective against An. stephensi (LC50 = 8.23, 12.34 and 16.37 µg/mL, respectively) followed by Ae. aegypti (LC50 = 9.03, 13.33 and 17.91 µg/mL), and Cx. quinquefasciatus (LC50 = 9.86, 14.49 and 19.50 µg/mL). Overall, this study adds knowledge to develop newer and safer natural larvicides against malaria, dengue and filariasis mosquito.
Keywords: biosafety